Analisis Framing Berita Basuki Tjahaja Purnama di Tempo.co dan Detik.com Edisi 13-26 November 2019 - Alfa Kumala (LPPM Stikosa-AWS, 2022)
Research on Appointment of Basuki Tjahaja Purnama as The BUMN commissioner harassed researchers to examine the issue. Where this study aims to find out how Tempo.co and Detik.com's attitude in constructing news coverage on an issue of the appointment of Basuki Tjahaja Purnama November 13 – November 26 2019 edition. This news contains the polemic of the appointment of Basuki Tjahaja Purnama as a commissioner of SOEs who reap the pros and cons. In this study, researchers used a qualitative framing analysis method modeled by Zhongdang Pan and Gerald M. Kosicki using Media Construction theory.The application of Zhongdang Pan and Gerald M. Kosicki framing analysis is divided into 4 structures, namely: Syntax, Script, Thematic, Rhetorical. If viewed syntactically, From the packaging of the news regarding the appointment of Basuki Tjahaja Purnama as a commissioner in BUMN, the two media are indeed very clear in terms of the level of sources. Scripturally, both of them contain several news items that are not accompanied by a complete 5W+1H element. Both media thematically and rhetorically also have differences in delivery to the reader. Tempo.co online media tends to put the contra's statement Basuki Tjahaja Purnama at the beginning of the news or in the middle of the news, then denied by the pro Basuki Tjahaja Purnama. This is done by including repetition of information from previously uploaded news. Detik.com contains only one source statement in one news.